1999
DOI: 10.1084/jem.190.7.1025
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitor of Death Receptor Signaling, Flice-Inhibitory Protein Defines a New Class of Tumor Progression Factors

Abstract: Death receptor–mediated apoptosis can be modulated by several antiapoptotic proteins, such as the FLICE (FADD [Fas-associated death domain]-like IL-1β–converting enzyme)-inhibitory proteins (FLIPs). The FLIP family includes both cellular and viral members. The Kaposi's sarcoma–associated herpesvirus protein (KSHV)-FLIP is expressed by human herpesvirus 8 (HHV-8), which is associated with malignancies such as Kaposi's sarcoma and certain lymphomas. In this paper, we demonstrate that KSHV-FLIP protects cells fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
270
1
5

Year Published

2000
2000
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(285 citation statements)
references
References 25 publications
(33 reference statements)
9
270
1
5
Order By: Relevance
“…Many of the proteins encoded by HHV-8 may also inhibit immune responses to the virus. For example, vFLIP blocks cytotoxic T-cell killing of HHV-8-infected cells by inhibiting Fas activation [43]; vMIP-II may restrict recruitment of Th1 lymphocytes to HHV-8-infected cells [44]; K1 may prevent class 2 MHC-mediated T cell activation by HHV-8 [45]; and K3 and K5 block cell surface display of class 1 MHC molecules on the cell surface [46]. Although the majority of cells within KS lesions show latent infection, a small subset expresses lytic cycle genes [47] and produce viral progeny [48].…”
Section: The Role Of Hhv-8mentioning
confidence: 99%
“…Many of the proteins encoded by HHV-8 may also inhibit immune responses to the virus. For example, vFLIP blocks cytotoxic T-cell killing of HHV-8-infected cells by inhibiting Fas activation [43]; vMIP-II may restrict recruitment of Th1 lymphocytes to HHV-8-infected cells [44]; K1 may prevent class 2 MHC-mediated T cell activation by HHV-8 [45]; and K3 and K5 block cell surface display of class 1 MHC molecules on the cell surface [46]. Although the majority of cells within KS lesions show latent infection, a small subset expresses lytic cycle genes [47] and produce viral progeny [48].…”
Section: The Role Of Hhv-8mentioning
confidence: 99%
“…Intracellular inhibition of CD95 apoptosis signaling by FLIP has been shown to favor tumor immune escape and to act as a tumor progression factor [13,14]. Although FLIP S efficiently inhibits CD95-mediated apoptosis, lck FLIP S -transgenic mice did not develop T cell lymphomas within their normal lifetime.…”
Section: Transgenic Overexpression Of Flip S Does Not Lead To Tumorigmentioning
confidence: 99%
“…Thus, c-FLIP L expression in tumor cells has been correlated with resistance to CD95-induced apoptosis in vitro and enhanced tumor progression in vivo [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…To impact the role of pro-survival proteins known to be NF-kB targets, we examined the expression of FLICE-inhibitory protein (FLIP) (Micheau et al, 2001) whose elevated expression has been shown to promote tumor establishment (Djerbi et al, 1999;Medema et al, 1999) and of members of the IAP family frequently overexpressed in tumors, i.e. IAP1, IAP2 and XIAP.…”
Section: Resultsmentioning
confidence: 99%